THE EFFECT OF A MIXTURE OF SELECTED NANOPOLLUTANTS ON THE LEVEL OF DNA DAMAGE IN THE BLOOD OF CYPRINUS CARPIO FRY - Gniadek , Anna; Chrobak , Daria (Collection of scientific papers «ΛΌГOΣ», 2023)
Chemical compounds, widely produced and released into aquatic ecosystems, pose threats to biocenosis and accumulate within food chains. This study examines the impact of four specific pollutants – ibuprofen, SDS, EE2, and DMSO on DNA damage in nine-month-old Cyprinus carpio fry. These pollutants are detected in groundwater, surface water, and drinking water. The study employs the Single Cell Gel Electrophoresis (Comet Assay) to analyze DNA damage levels resulting from exposure to the pollutants. The chosen fish species, serves as a suitable model due to its resilience to diseases and exposure to mutagenic substances. Results indicate a dose-dependent reduction in DNA content in response to pollutant exposure. This research highlights the urgent need to assess the genetic impact of pollutants on aquatic ecosystems and emphasizes the importance of understanding the risks posed by these contaminants.